PASSENGERS’ SATISFACTION WITH THE LAGOS SHUTTLE TRAIN SERVICES, LAGOS, NIGERIA - Olorunfemi Ayodeji OLOJEDE; Sikiru Akintunde FOLORUNSO; Adewale Sheyi POPOOLA; Peter Bolaji OLADEJI; Olamide AKINTIFONBO; Damilare Jeremiah ODEYEMI (Scientific Journal of Silesian University of Technology. Series Transport)
The study assessed passengers’ satisfaction with the services of the Lagos Shuttle Train Services in Lagos, Nigeria. Two types of train, the Mass Transit Train (MTT) and the Diesel Multiple Unit (DMU), were covered. Using multistage sampling, 246 passengers were surveyed. It was found that the DMU passengers had higher socioeconomic profiles; the overall condition of the DMU was also better. Further analyses reveal that passengers’ satisfaction differed for the train types: the MTT passengers were more particular about the operational environment, while the DMU passengers were concerned with both physical characteristics and the operational environment. Generally, passengers were satisfied with accessibility, coverage, fare, safety at station and onboard, security at station, and security of luggage; however, the Lagos Shuttle Train Services was found wanting on several key indicators. Recommendations are proffered towards enhancing the service quality of the Lagos Shuttle Train Services.